Modeling of a hybrid electric vehicle - Ng, Yao Hua. (2012)
This project focuses on the modeling and simulation of an automotive vehicle. Vehicle powertrain and driveline components were modeled for simulation; controlling of vehicle speed via a PI speed controller. Modern vehicle Anti-Lock Braking System was also modeled; simulation was conducted on the Anti-lock